A three-state model for describing the temperature variation of the scintillation properties of Cs2HfCl6. (31st January 2018) - Koshimizu, Masanori; Saeki, Keiichiro; Fujimoto, Yutaka; Okada, Go; Yanagida, Takayuki; Yamashita, Shinichi; Asai, Keisuke
Abstract: The temperature dependence of the scintillation intensity of Cs2 HfCl6 was measured and found to increase monotonically from 10 to 300 K, whereas no significant dependence on temperature was observed for the scintillation decay. A simple three-state model in which two excited levels are slightly different in their energies and have similar radiative rates was able to describe the experimental trends. The model is consistent with the experimental observation of two kinds of V k centers and with theoretical predictions of two types of self-trapped excitons reported in the literature.